2017
DOI: 10.1039/c7ta03424e
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired interfacial reinforcement of polymer-based energetic composites with a high loading of solid explosive crystals

Abstract: In this work, inspired by the strong chemical adhesion of mussels, a facile and noncovalent in situ polymerization of dopamine approach has been employed to coat 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…61 In this regard, enhanced roughness was noted from the SEM images aer the addition of f-PJC reinforcement to the composites; this may be due to the heterogeneity of the composites with increasing addition of f-PJC content, and it can also remove air voids through a de-bonding mechanism. 62,63 In accordance with a previous report, 64 it was also concluded that the matrix contact angle is greater than 90 ; additionally, further improvement in the roughness of the surface appears to improve the contact angle and, thus, improved hydrophobic character of the resulting composites was observed. In addition, the increased hydrophobic properties of the prepared PETEP-CBz polymer composites may be due to improved cross-linked density and decreased porosity in the polymer matrix with respect to the increased quantity of amine-functionalized Prosopis juliora carbon (f-PJC) in the composite materials.…”
Section: Rtsupporting
confidence: 89%
“…61 In this regard, enhanced roughness was noted from the SEM images aer the addition of f-PJC reinforcement to the composites; this may be due to the heterogeneity of the composites with increasing addition of f-PJC content, and it can also remove air voids through a de-bonding mechanism. 62,63 In accordance with a previous report, 64 it was also concluded that the matrix contact angle is greater than 90 ; additionally, further improvement in the roughness of the surface appears to improve the contact angle and, thus, improved hydrophobic character of the resulting composites was observed. In addition, the increased hydrophobic properties of the prepared PETEP-CBz polymer composites may be due to improved cross-linked density and decreased porosity in the polymer matrix with respect to the increased quantity of amine-functionalized Prosopis juliora carbon (f-PJC) in the composite materials.…”
Section: Rtsupporting
confidence: 89%
“…However, the compressive strength of LLM‐105‐SR was noticeably improved to 77.8 MPa, displaying a 62.5 % increase. Such fairly high compressive strength is not commonly observed for current pressed PBXs , indicating that the LLM‐105‐SR with regular spherical morphology and rough surface can result outstanding compressive behaviors. As for the tensile tests, it is gratifying to note that both the LLM‐105‐SS and LLM‐105‐SR witnessed an evident increase of the tensile strength and strain.…”
Section: Resultsmentioning
confidence: 80%
“…Thus, new materials must be found with strong adhesion for modifying energetic crystal particles. Recently, mussel coatings inspired by dopamine in situ polymerization attracted interest and are usually used to passivate large amounts of substrates such as glass, metals, polymers, and nano-carbon materials [18][19][20][21][22][23][24][25]. Dopamine chemistry was reported for crystal modification of energetic materials, such as HMX, RDX, and 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) [11,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%